Pembelajaran SOLE dalam Membangun Keefektifan Belajar pada Peserta Didik - Aura Fariha (Edudikara: Jurnal Pendidikan dan Pembelajaran, 2021)
The purpose of this paper is to build the effectiveness of learning in students through the SOLE (Self Organizing Learning Environment) learning model. During the Covid-19 pandemic, the learning concept system was changed to online (Online) to keep the learning process running and conveyed to students optimally. Through online learning (Online) or BDR (Learning from Home) or PJJ (Distance Learning) students can still access learning perfectly and achieve competency indicators. Many parents face obstacles in online learning due to independence in children (students) and in participating in online learning (Online). The solution obtained from this analysis is to embed the SOLE (Self Organizing Learning Environment) learning model which emphasizes the independence of each student. This SOLE learning model has a goal in forming competencies (skills) in students, including 1. Critical thinking 2. Problem solving ability 3. Communication skills, and in the SOLE learning model there are three stages of learning activities: 1. Questions 2. Investigation 3. Reviewing the three stages of the activity can create the effectiveness of students in receiving the material. By embedding learning the SOLE (Self Organizing Learning Environment) model is very helpful in the learning process from home (Online) students have the main role to be active in every learning and instill an independent attitude and learning effectiveness in students.